The Effect of Company Size on The Disclosure of Sustainability Reports in Mining Companies - Hendri Maulana; Gita Puspita; Erlina Sari Pohan; Maria Lusiana Yulianti (Greenation International Journal of Economics and Accounting, 2023)
Sustanability Reports in Indonesia have experienced development, with the existence of strict rules that require companies to carry out social and environmental responsibilities that will encourage company managers to disclose sustainability reports. However, these reasons do not make all companies in Indonesia disclose sustainability reports. Each company manager has a different level of initiative to disclose a sustainability report. Company size as one of the characteristics of a company that also determines the level of investor confidence, requires good credibility so that companies need to contribute to economic, social and environmental growth. Research objectives To determine the effect of company total assets on sustainability report disclosure, to determine the effect of company total sales on sustainability report disclosure, to determine the effect of company size on sustainability report disclosure. This type of research is quantitative. The population in this study were mining companies listed on the Indonesia Stock Exchange in 2017-2018. The sampling technique used was a purposive sampling technique.